Controlling the photoluminescence spectra of porous nc-Si–SiOx structures by vapor treatment - Dan’ko, V.A.; Bratus, V.Ya.; Indutnyi, I.Z.; Lisovskyy, I.P.; Zlobin, S.O.; Michailovska, K.V.; Shepeliavyi, P.E. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2010)
The effect of HF and H₂O₂ vapor treatment on the spectral composition and
intensity of photoluminescence (PL) in porous oblique deposited nc-Si–SiOx structures
have been studied using FTIR, electron-spin resonance (EPR) and PL measurements. As
a result of HF vapor treatment, considerable PL intensity growth and blueshift of PL
peak position are observed. It is suggested that the evolution of the PL spectra in HF
vapor-treated samples can be attributed to selective-etching-induced decrease in Si
nanoparticle dimensions and to passivation of Si dangling bonds (that are nonradiative
recombination trap states) by hydrogen and oxygen. Additional treatment in H₂O₂ vapor
results in additional nc-Si surface oxidation and reduction of nc-Si size. The possibility to
control the PL characteristics (peak position and intensity) of the porous nc-Si–SiOx
structures in a wide range by above treatments is shown.